1999
DOI: 10.1002/(sici)1096-9071(199902)57:2<198::aid-jmv19>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic influenza viral double-stranded RNA induces an acute-phase response in rabbits

Abstract: Numerous studies have characterized the physiological effects of synthetic, high-molecular-weight, homopolymeric, double-stranded RNA (dsRNA), particularly polyriboinosinic.polyribocytidylic acid [Carter and De Clercq (1974): Science 186:1172-1178], but limited information exists regarding the physiological effects of dsRNA of viral composition and size. In this report, we determined sleep and fever responses of rabbits to intracerebroventricular injection of different doses of synthetic viral dsRNA (either 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 16 publications
0
12
0
Order By: Relevance
“…We have demonstrated that the response of rabbits to ICV virus-associated dsRNA extracted from influenza-infected lung (Majde et al, 1991) is similar to the response to poly [rI Á rC]. We have also demonstrated that the APR induced by synthetic influenza dsRNA resembles the APR induced by poly[rI Á rC], though the much smaller viral dsRNA fragments are considerably less potent than high molecular weight poly[rI Á rC] (Fang et al, 1999). The rabbit APR induced by all of these forms of dsRNA is similar to that induced by large doses of IV abortive influenza virus (Kimura-Takeuchi et al, 1992a), which may synthesize dsRNA during partial replication.…”
Section: Introductionmentioning
confidence: 81%
“…We have demonstrated that the response of rabbits to ICV virus-associated dsRNA extracted from influenza-infected lung (Majde et al, 1991) is similar to the response to poly [rI Á rC]. We have also demonstrated that the APR induced by synthetic influenza dsRNA resembles the APR induced by poly[rI Á rC], though the much smaller viral dsRNA fragments are considerably less potent than high molecular weight poly[rI Á rC] (Fang et al, 1999). The rabbit APR induced by all of these forms of dsRNA is similar to that induced by large doses of IV abortive influenza virus (Kimura-Takeuchi et al, 1992a), which may synthesize dsRNA during partial replication.…”
Section: Introductionmentioning
confidence: 81%
“…DsRNA length effects were observed in vesicular stomatitis virus-infected mouse embryonic fibroblasts (MEFs), where longer in vitro transcribed dsRNA molecules resulted in lower EC 50 values than did molecules of shorter lengths and in uninfected MEFs IFN and ISG transcripts were induced in a dsRNA length dependent manner [11]. A study in rabbits found that longer dsRNA molecules induced greater somnogenic and pyrogenic responses compared to shorter molecules [14]. Similar to what has been observed here in fish, poly I:C and in vitro transcribed dsRNA induce similar but not exactly the same innate immune responses in mammals [11,19].…”
Section: Discussionmentioning
confidence: 99%
“…Mengo viral dsRNA is also toxic in vivo, (28) indicating that it is resistant to mixed tissue nucleases. Studies by my research group confirm that dsRNA of viral composition is stable in vivo and that fragments as small as 108 bp are capable of inducing an APR, (29) although at doses 100-fold higher than those required for high molecular weight poly[rI ? rC].…”
Section: Physical Features Of Biologically Active Dsrnamentioning
confidence: 97%
“…rC], (45-4 8) by low molecular weight dsRNA (309 bp) of mixed base composition, (12 ) and presumably by comparable virus-associated dsRNA capable of inducing an APR. (29,49) Early gene induction by poly[rI ? rC], including induction of the chemokine IP-10, is independent of its induction of IFN or any other proteins, but later gene induction requires protein synthesis and IFN production.…”
Section: Systemic Toxicity Of and Cytokine Induction By Dsrnamentioning
confidence: 99%
See 1 more Smart Citation